2016
DOI: 10.1111/liv.13237
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of hepatitis E outbreaks: a systematic review

Abstract: Hepatitis E virus (HEV) is responsible for repeated water-borne outbreaks since the past century, representing an emerging issue in public health. However, the global burden of HEV outbreak has not been comprehensively described. We performed a systematic review of confirmed HEV outbreaks based on published literatures. HEV outbreaks have mainly been reported from Asian and African countries, and only a few from European and American countries. India represents a country with the highest number of reported HEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 119 publications
(385 reference statements)
1
95
0
Order By: Relevance
“…It is one of the most common causes of acute viral hepatitis in the world. Although the infection is generally self‐limiting, severe complications and high mortality rates have been reported in special populations, including pregnant women, immunocompromised patients, and patients with preexisting liver disease . HEV outbreaks periodically occur throughout resource‐limited countries, including the large ongoing outbreak in Niger, resulting in a heavy clinical burden with a high mortality rate in pregnant women .…”
mentioning
confidence: 99%
“…It is one of the most common causes of acute viral hepatitis in the world. Although the infection is generally self‐limiting, severe complications and high mortality rates have been reported in special populations, including pregnant women, immunocompromised patients, and patients with preexisting liver disease . HEV outbreaks periodically occur throughout resource‐limited countries, including the large ongoing outbreak in Niger, resulting in a heavy clinical burden with a high mortality rate in pregnant women .…”
mentioning
confidence: 99%
“…However, is some cases, particularly in pregnant women, hepatitis E can cause acute liver failure, and recently hepatitis E outbreaks have become more common in displacement camps (Boccia et al, 2006;Hakim et al, 2016).…”
Section: Outbreak Burden and The Role Of Washmentioning
confidence: 99%
“…Large and prolonged HEV outbreaks are frequently seen in Asian and African countries. 2 It has been suggested that Hecolin® could be valuable in preventing severe morbidity and mortality in this epidemic setting, such as in a recent outbreak in Nepal. 95,96 However, the effectiveness of HEV vaccine is not known to provide a quick protection for the exposed populations during HEV outbreaks.…”
Section: T Cell Exhaustion In Chronic Hepatitis Ementioning
confidence: 99%
“…Hepatitis E virus (HEV) infection is the predominant cause of acute hepatitis worldwide . It is also the causative agent of many large hepatitis outbreaks and continuously poses a serious threat, especially in developing countries . HEV was initially thought to only cause acute infection where most patients remain asymptomatic .…”
Section: Introductionmentioning
confidence: 99%